Психоаналитические концепции эмоционального выгорания - Laikova, Irina V. (Rossijskij psihologičeskij žurnal., 2016)
The article describes the psychoanalytic concepts of study of the burnout phenomenon, which are based on qualitative approach. This approach is complementary to studies concentrated in the Yeld of organizational and social psychology which are mostly quantitative by nature and give limited insight into the dynamics of burnoutand personal meanings, associated with it. Psychoanalytic studies mainly address two aspects of burnout, namely a disruption of professional identity of people and diZculties at the intersubjective level which are closely interlinked. The tripartite conceptual model of S. Vanheule and P. Verhaeghe is shown which is based on the schema of J. Lacan’s “two mirrors” re[ecting three dynamic rocesses accompanying subjective experience of “burned out” professionals. Alternative models and explanatory concepts of burnout concordant with presented dynamic processes are considered. According to J. Lacan, the processes re[ect the functioning of the mental instances of the Ego, ideal Ego, Ego-ideal and Superego in the process of an increment of subjective knowledge. In the light of the psychoanalytic concepts, emotional burnout is treated as a crisis of identity, generated from the problems of formation of subjectivity in intersubjective interactions. This, in turn, allows to attribute emotional burnout as a general psychological phenomenon, not solely related to the professional activities. The basis of emotional burnout lies in the unconscious con[ict between conscious needs and unconscious drives resulting in the blocking activityand the alienation of the subject from certain aspects of his being. IdentiYcation and analysis of unconscious contradictions, leading to a tension and stagnation of the subject, seems to be promising for prevention and overcoming of the burnout. В статье рассмотрены психоаналитические концепции исследования феномена эмоционального выгорания, которые основываются на качественном подходе. Такой подход комплементарен к исследованиям, сосредоточенным в области организационной и социальной психологии, носящим преимущественно количественный характер и дающим ограниченное представление о динамике выгорания и личностных смыслах, связанных с ним. Психоаналитические исследования, в основном, касаются двух аспектов эмоционального выгорания – нарушения профессиональной идентичности  и трудностей на интерсубъективном уровне, которые тесно связаны между собой. Показана трехсторонняя концептуальная модель S. Vanheule и P. Verhaeghe на основе схемы из «двух зеркал» Ж. Лакана, отражающая три динамических процесса, сопровождающих субъективные пережива- ния «выгоревших» профессионалов. Приведены альтернативные модели  и объяснительные концепции эмоционального выгорания, соотносимые с представленными динамическими процессами, отражающими, согласно Ж. Лакану, функционирование психических инстанций Эго, идеального Эго, Эго-идеала и Супер-Эго в процессе приращения субъективного знания. В свете психоаналитических концепций эмоциональное выгорание трактуется как кризис идентичности, порождаемый проблемами формирования субъектности в интерсубъективных взаимодействиях, что позволяет атрибутировать эмоциональное выгорание как общепсихологический феномен, не связанный исключительно с профессиональной деятельностью. Основой эмоционального выгорания представляется неосознаваемый конфликт между сознательными потребностями и бессознательными влечениями, в результате которого происходит блокирование активно- сти и отчуждение субъекта от некоего своего аспекта бытия. Выявление и анализ бессознательных противоречий, приводящих субъекта к напря- жению и стагнации, представляется перспективным для профилактики и преодоления эмоционального выгорания.